2008
DOI: 10.1242/jcs.038570
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SUMO1 in mice affects RanGAP1 localization and formation of PML nuclear bodies, but is not lethal as it can be compensated by SUMO2 or SUMO3

Abstract: Conjugation of the small ubiquitin-like modifier (SUMO) to target proteins regulates numerous biological processes and has been implicated in tumorigenesis and metastasis. The three SUMO isoforms in vertebrates, SUMO1 and the highly similar SUMO2 and SUMO3, can be conjugated to unique as well as overlapping subsets of target proteins. Yet, it is still not clear whether roles for each family member are distinct or whether redundancy exists. Here we describe a mutant mouse line that completely lacks SUMO1, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(125 citation statements)
references
References 46 publications
10
115
0
Order By: Relevance
“…The SUMO2 mRNA accounts for 80% of the entire SUMO mRNA pool in total mouse embryos at E7.5, whereas SUMO3 is only expressed at very low levels (2%) [18]. SUMO1 -/-mice are also viable and fertile and lack any obvious phenotype, indicating that the SUMO2 pool is able to compensate for the absence of SUMO1 [19,20]. Mating experiments between the different knockout mice further indicated that the different SUMO family members functionally compensated for each other [18].…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 99%
“…The SUMO2 mRNA accounts for 80% of the entire SUMO mRNA pool in total mouse embryos at E7.5, whereas SUMO3 is only expressed at very low levels (2%) [18]. SUMO1 -/-mice are also viable and fertile and lack any obvious phenotype, indicating that the SUMO2 pool is able to compensate for the absence of SUMO1 [19,20]. Mating experiments between the different knockout mice further indicated that the different SUMO family members functionally compensated for each other [18].…”
Section: Twenty Years Of Sumo Research In Cell Cycle Controlmentioning
confidence: 99%
“…Second, deficiency of UBC9 causes lethality and it is important for cell cycle progression and growth, probably by modulation of the degradation of mitotic cyclins (Nacerddine et al, 2005;Nowak and Hammerschmidt, 2006;Seufert et al, 1995). Yet, in contrast to the loss of UBC9 (Alkuraya et al, 2006), the loss of the UBC9 substrate SUMO1 has been shown to not cause any overt physiological and morphological phenotypes in the mouse (Evdokimov et al, 2008;Zhang et al, 2008), with the exception of a discordant study (Alkuraya et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…RanGAP1 helps to accelerate the GTP hydrolysis function of Ran GTPase, converting Ran‐GTP to Ran‐GDP and promoting the activation of import carriers 21. The loss of SUMOylation of RanGAP1 likely results in the loss of localization at the nuclear pore complex and loss of function of RanGAP1 22, 23. We also found a decrease in nuclear TDP‐43 in the ALS8 fibroblasts.…”
Section: Discussionmentioning
confidence: 54%